Interreligious Solidarity in South Africa: Analyzing the Role of the Muslim Community - Omar, A. Rashied (Interreligious studies and intercultural theology, 2023)
South Africa has a unique and vibrant interreligious solidarity movement. During the late 1980s and early 1990s, the interreligious movement played a significant role in the anti-apartheid struggle via the South African Chapter of the World Conference of Religions for Peace. Since the onset of a non-racial and democratic dispensation in 1994, the interreligious movement forms an integral part of South Africa's burgeoning civil society, attempting to hold the post-apartheid government accountable for its political and moral mandate. This article explores the development of South Africa's interreligious movement with special reference to the role of the Muslim community. It argues that, relative to its small size, the local Muslim community has played a disproportionate role in shaping the history and trajectory of the South African interreligious solidarity movement during the anti-apartheid struggle (1948-1994) and in the contemporary democratic period (1994-2023).